Employee Engagement in a Multigenerational Workforce at Hospital X - Kristi, Gandhi; Basabih, Masyitoh (Universitas Muhammadiyah Yogyakarta, 2024)
As the organization grows each year, the workforce will continue to change. New hires may come from older or younger generational groups, leading to a multigenerational workforce in the organization. It is known that each generational group has different characteristics that can affect employee engagement per generation in the workplace. This study aims to determine the depiction of the multigenerational workforce and employee engagement in the multigenerational workforce at the hospital. This study used a cross-sectional study and was conducted by distributing online questionnaires to health workers who worked at Hospital X. The results found that a multigenerational workforce is apparent in Hospital X. It was also found that the oldest generation group in the hospital, Generation X, had the highest average engagement score. Through analysis, a significant relationship was also found between the multigenerational workforce and employee engagement. The discovery of a multigenerational workforce and differences in the level of employee engagement in generational groups indicates that hospital management must take advantage of the diversity that exists. Strategies are also needed to increase and maintain employee engagement in each generational group.